Application of nanoindentation to characterize creep behavior of oil shales - Kouqi Liu; Mehdi Ostadhassan; Bailey Bubach (Journal of Petroleum Science and Engineering, 2018)
In petroleum industry, creep behavior of rocks can affect the fracture conductivity, well productivity and ultimate recovery of the reservoir, in shale formations in particular. To get a better insight into this phenomenon, in this study, we applied grid nanoindentation method as a function of time to quantify creep behavior of shale rocks which is a complex material. The deconvolution results from statistical analysis of the data showed that shale samples could be distinguished by three mechanical phases where the mechanical phase with the largest hardness value exhibits the least creep deformation. Burgers models was applied to characterize the creep behavior of our shale samples. We realized as creep time increases, the creep time constant value increases, therefore, a logarithmic function can be used to quantify their correlations. This study showed that as the creep time increases, Young's modulus, hardness, and fracture toughness will decrease. Finally, we concluded, shale samples become softer and more prone to fracture growth as the creep time increases.
Keywords: Creep; Deconvolution; Mechanical properties; Nanoindentation; Oil shales